Writing for broadcast journalists - Thompson, Rick, 1947- (Milton Park, Abingdon ; New York : Routledge, 2010)
Guides readers through the significant differences between the written and the spoken versions of journalistic English. This title helps broadcast journalists at different stages of their careers to avoid such pitfalls as the use of newspaper-English, common linguistic errors, and Americanised phrases.
Introduction -- Good spoken English -- The language of broadcast news -- Writing broadcast news scripts -- Different techniques for radio and television -- Writing online news -- And finally--
Includes bibliographical references and index.
Keywords: Broadcast journalism -- Authorship; Reporters and reporting; Report writing